Evolutionary game analysis on safety supervision for coal mine considering speculative behavior - Tu, Jun; Shi, Qiufeng; Li, Meiqi; Li, Jingming (IEEE access, 2024)
This paper considers the speculative behavior of coal mining enterprises and regulatory authorities, and uses evolutionary game theory to study safety supervision in production process of coal mine. It describes the game strategies of coal mining enterprises and regulatory authorities as safety production investment and safety supervision investment respectively. The four game scenarios are defined based on the different speculations of the two parties. The evolutionary game model is established and solved. The evolutionary game analysis is performed, and the conditions that the system evolves to four stable points are obtained. The numerical simulations are used to further analyze the influence of the parameters. The results show that when the parameters meet different conditions, the system evolves to four different stable points. The smaller the number of individuals in the regulatory authorities who choose speculative strategy, the more favorable it is for coal mining enterprises to make normal investment. The more underestimated the supervision power of the regulatory authorities, the more inclined the coal mining enterprises are to adopt speculative strategies. The higher the regulatory authorities' assessment of the safety investment of coal mining enterprises, the more inclined regulatory authorities are to adopt speculative strategies.